MiR‐196a regulates the skin pigmentation of koi carp (Cyprinus carpio L.) by targeting transcription factor mitfa. (15th September 2020) - Yin, Haoran; Luo, Mingkun; Luo, Wentao; Wang, Lanmei; Zhu, Wenbin; Fu, Jianjun; Dong, Zaijie
Abstract: MicroRNAs (miRNAs) are endogenous small non‐coding RNAs that play important roles in many biological processes. The function of miRNAs in skin colour differentiation and pigmentation has been reported in many animals. However, the researches about their molecular mechanisms of regulating the formation of different skin colour of koi carp ( Cyprinus carpio L.) are deficient. In this study, we detected the temporal and spatial expression levels of ccr‐miR‐196a (hereinafter referred to as miR‐196a) and then predicted its target mRNA of microphthalmia‐associated transcription factor a ( mitfa ), which is a key regulatory transcript factor in the melanogenesis pathway, with bioinformatics and dual‐luciferase reporter methods. Furthermore, we silenced the miR‐196a in vivo with an antagomir to detect whether the miR‐196a would affect the expression levels of mitfa mRNA and its downstream genes including tyrosinase ( tyr ), tyrosinase‐related protein 1 ( tyrp 1) and dopachrome tautomerase ( dct ). The results revealed that mitfa and its downstream genes' mRNA expressions all significantly increased in the treatment group compared with the control group. We presumed that miR‐196a might regulate the pigmentation of koi carp through targeting the mitfa . The finding provided the fundamental information regarding miRNA–mRNA interaction on different skin colour pigmentation in koi carp.